The Influence of Social Media on Purchasing Decisions - Gatot Wijayanto; Jushermi Jushermi; Arwinence Pramadewi; Arini Novandalina; Yutiandry Rivai (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
Consumer decision-making is an integration process that uses information to assess and choose one of two or more alternative actions. This integration process yields a choice, which is presented cognitively as a desire to act. The fall in sales over the last two years undermines this study. This drop in sales is attributed to the absence of social media, which corresponds to the 6C: context, content, community, customization, communication, commerce, and connection, as well as changes in consumer perception of product quality, which leads to a decrease in purchasing decisions.According to the findings of this study, customers rate the usage of social media and product quality as pretty excellent, and they